The Mental Health Mandate: Evaluating the Legal Requirement for Psychological Support Services within Higher Education Institutions - Nurphi, Meiria (STIT Pringsewu, 2026)
As global reports indicate clinically significant levels of mental disorder symptoms among university students, higher education institutions (HEIs) are increasingly positioned as front-line mental health responders. However, the legal basis for this expectation remains fragmented and contested. This study employs a dual-method approach, qualitative doctrinal analysis and a systematic literature review, to evaluate the legal mandates for psychological support in the US, UK, and EU. Findings indicate that while a universal right to therapy is absent, a de facto mandate has emerged through disability and equality laws, which categorize mental health support as an enforceable